Modelling and statistical analysis of YouTube's educational videos: A channel Owner's perspective. (January 2019) - Saurabh, Samant; Gautam, Sanjana
Abstract: YouTube is one of the most popular websites. It is a vast resource for educational content. To better understand the characteristics and impact of YouTube on education, we have analyzed a popular YouTube channel owned by the author of this paper. It has thousands of subscribers, millions of views, and hundreds of video lectures. We have used our private YouTube analytics data to provide an in-depth study of YouTube educational videos. Our analysis provides valuable information that can have major technical and commercial implications in the field of education. We perform in-depth time-series analysis of the channel data to reveal the trend, seasonality and temporal pattern for the educational videos on YouTube. In our study, we find the relationship between video uploading activity, channel's age and its popularity. We use an entropy-based decision tree classifier to find the features that are most important for the popularity of videos. We show that video rank and number of views follow the Zipf distribution for educational videos. We observe a strong correlation between the geographical location of viewers and the location of industry the channel caters to. Besides, we also provide knowledge regarding the popular devices and operating systems used for viewing the educational videos, main traffic sources, playback locations, translation activity, and demography of viewers. Overall, we believe that the results presented in this paper are crucial in understanding YouTube EDU videos characteristics which can be utilized for making well-informed decisions for improving educational content and learning technologies. Highlights: Periodicity and trend analysis of YouTube education video viewership. Effect of Video Upload Activity and age of channel on its Viewership. The Effect of Video Length, average percentage viewed and translation. YouTube Educational videos rank distribution follow Zipf Distribution. Statistics regarding devices, OS, traffic sources, playback location and demography.